2011
DOI: 10.1051/0004-6361/201016348
|View full text |Cite
|
Sign up to set email alerts
|

Mass, light and colour of the cosmic web in the supercluster SCL2243-0935 (z = 0.447)

Abstract: AstrophysicsMass, light and colour of the cosmic web in the supercluster SCL2243-0935 (z = 0.447) , ABSTRACTAims. In archival 2.2 m MPG-ESO/WFI data we discovered several mass peaks through weak gravitational lensing, forming a possible supercluster at redshift 0.45. Through wide-field imaging and spectroscopy we aim to identify the supercluster centre, confirm individual member clusters, and detect possible connecting filaments. Methods. Through multi-colour imaging with CFHT/Megaprime and INT/WFC we identif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 58 publications
2
51
1
Order By: Relevance
“…They are lower than the masses of very rich superclusters such as the Shapley supercluster, the Corona Borealis supercluster, and other very rich superclusters (Reisenegger et al 2000;Proust et al 2006;Ragone et al 2006;Pearson et al 2014;O'Mill et al 2015). The mass-to-light ratios of the SGW superclusters, M/L ≈ 300 h M /L , are close to the values of the mass-to-light ratios for other rich superclusters (Gavazzi et al 2004;Schirmer et al 2011;Einasto et al 2015). Moreover, the components in rich SGW superclusters have masses that are comparable to the masses of simulated superclusters of average richness (Chon et al 2014;Araya-Melo et al 2009).…”
Section: Discussion and Summarymentioning
confidence: 70%
See 1 more Smart Citation
“…They are lower than the masses of very rich superclusters such as the Shapley supercluster, the Corona Borealis supercluster, and other very rich superclusters (Reisenegger et al 2000;Proust et al 2006;Ragone et al 2006;Pearson et al 2014;O'Mill et al 2015). The mass-to-light ratios of the SGW superclusters, M/L ≈ 300 h M /L , are close to the values of the mass-to-light ratios for other rich superclusters (Gavazzi et al 2004;Schirmer et al 2011;Einasto et al 2015). Moreover, the components in rich SGW superclusters have masses that are comparable to the masses of simulated superclusters of average richness (Chon et al 2014;Araya-Melo et al 2009).…”
Section: Discussion and Summarymentioning
confidence: 70%
“…Johnston-Hollitt et al 2008;Schirmer et al 2011;Pompei et al 2016;Einasto et al 2015). They are lower than the masses of very rich superclusters such as the Shapley supercluster, the Corona Borealis supercluster, and other very rich superclusters (Reisenegger et al 2000;Proust et al 2006;Ragone et al 2006;Pearson et al 2014;O'Mill et al 2015).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Few superclusters at very high redshifts have already been discovered in deep, wide-field imaging surveys (Nakata et al 2005;Swinbank et al 2007;Gal et al 2008;Tanaka et al 2009;Schirmer et al 2011). Deep surveys like the ALHAMBRA project (Moles et al 2008) will provide us with data about (possible) very distant superclusters; we can analyse their structure and compare that with the local superclusters, using morphological methods.…”
Section: Discussionmentioning
confidence: 99%
“…Superclusters are important tracers of dark and baryonic matter in the Universe (Zappacosta et al 2005;Génova-Santos et al 2005;Heymans et al 2008;Buote et al 2009;Padilla-Torres et al 2009;Schirmer et al 2011). Studies of superclusters and of the supercluster-void network have demonstrated the presence of a characteristic scale in the distribution of rich superclusters (Einasto et al 1994(Einasto et al , 1997a.…”
Section: Introductionmentioning
confidence: 99%
“…Superclusters, with their high-density environment and complex inner structure, are excellent laboratories with which to study the properties and evolution of galaxies and the groups of galaxies in them (Einasto et al 2007b(Einasto et al , 2008(Einasto et al , 2014Schirmer et al 2011;Swinbank et al 2007;Gal et al 2008;Faloon et al 2013;Krause et al 2013;Luparello et al 2013;Chon et al 2014;Chow-Martínez et al 2014;Lee et al 2015).…”
Section: Introductionmentioning
confidence: 99%